Specialist palliative care services for older people in primary care: A systematic review using narrative synthesis. (January 2020) - de Nooijer, Kim; Penders, Yolanda WH; Pivodic, Lara; Van Den Noortgate, Nele J; Pype, Peter; Van den Block, Lieve
Background: There is recognition that older people with incurable conditions should have access to specialist palliative care services. However, it remains unclear which activities and outcomes these services entail for older people in primary care and to which patients they are provided. Aim: The aim of this review was to identify the criteria for referral to specialist services; who provides specialist palliative care; through which activities and with which frequency; which outcomes are reported; and which suggestions are made to improve services. Design: Systematic review of the literature and narrative synthesis. Quality appraisal and selection of studies were performed independently by two researchers. Participant characteristics, intervention features, outcome data and suggestions for improvement were retrieved. Data sources: Embase, Medline, Web of Science, Cochrane, Google Scholar, PsycINFO and CINAHL EBSCO databases (until June 2019). Results: Ten eligible articles, three qualitative, three quantitative, three mixed-method and one narrative review, were identified. Referral criteria were mainly based on patient characteristics such as diagnosis. The specialist services involved a variety of activities and outcomes and descriptions were often lacking. Services could be improved regarding the information flow between healthcare professionals, greater in-depth palliative care knowledge for case managers and social workers, identification of a key worker and support for family carers. Conclusion: The limited evidence available shows areas for improvement of the quality of and access to specialist services for older people, such as support for family carers. In addition, this review underscores the need for comprehensive reporting of interventions and the use of consensus-based outcome measures.